Reflections and data on abortion in Colombia - Mier Corpas, Ever David (2023)
Before 2006 Colombia was discussed in a social, moral and ethical dilemma on the decriminalization of abortion in favor of women and even after approved only jurisprudential three aspects. The country is still biased and voices that support their arguments doctrines argue freedom of women as absolute standard forgetting that the person has rights from the start to be conceived heard. On the other hand, there are those who defend or try to prove that abortion in its three forms is unnecessary, proposing solutions to the problem of various kinds, they can be moral, ethical and even religious alternatives. The purpose of this paper is to show the successes and failures in a very objective manner, the approval of abortion in its three forms established by the Constitutional Court of Colombia, progress and solutions to the problem.